2009
DOI: 10.1021/np800724h
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal Phloroglucinols from the Fern Elaphoglossum piloselloides

Abstract: Two new bicyclic phloroglucinols were isolated from the diethyl ether extract of an Argentine collection of the fern Elaphoglossum piloselloides. Structures were established by analysis of their spectroscopic data ((1)H NMR, HRMS, IR) and chemical derivatization. Both compounds show an acute molluscicidal activity against the schistosomiasis vector snail Biomphalaria peregrina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 14 publications
(26 reference statements)
4
57
0
Order By: Relevance
“…The acylphloroglucinols (Fig. 26) are found in E. lindbergii (Socolsky et al 2011a(Socolsky et al , 2016, E. yungense (Socolsky et al 2010a, b), E. piloselloides (Socolsky et al 2009) and E. gayanum (Socolsky et al 2010b). Specially, the prenylated acylphloroglucinols, elaphogayanin A-B, elaphopilosin C-E, lindbergins A-F and yungensins A-F were identified from E. gayanum (Socolsky et al 2010b), E. piloselloides (Socolsky et al 2010b), E. lindbergii (Socolsky et al 2011a(Socolsky et al , 2015 and E. yungense (Socolsky et al 2010a).…”
Section: Lindsaeaceaementioning
confidence: 99%
“…The acylphloroglucinols (Fig. 26) are found in E. lindbergii (Socolsky et al 2011a(Socolsky et al , 2016, E. yungense (Socolsky et al 2010a, b), E. piloselloides (Socolsky et al 2009) and E. gayanum (Socolsky et al 2010b). Specially, the prenylated acylphloroglucinols, elaphogayanin A-B, elaphopilosin C-E, lindbergins A-F and yungensins A-F were identified from E. gayanum (Socolsky et al 2010b), E. piloselloides (Socolsky et al 2010b), E. lindbergii (Socolsky et al 2011a(Socolsky et al , 2015 and E. yungense (Socolsky et al 2010a).…”
Section: Lindsaeaceaementioning
confidence: 99%
“…These crosspeaks are useful to identify the acyl group located at C-6 in acylphloroglucinol derivatives that possess an acylfilicinic acid-type ring. [2][3][4] This empirical observation can be useful to identify such residues in phloroglucinols containing three or more rings. The location of the acyl groups was established through HMBC correlations observed between 5-OH and both C-14 and C-14′′.…”
Section: Introductionmentioning
confidence: 95%
“…1 Our previous chemical studies on E. piloselloides, E. gayanum, and E. yungense showed that all of them contain acylphloroglucinols in their scales, rhizomes, and roots. [2][3][4] In the last decades, attention has been drawn to these compounds due to their various biological activities, such as antidepressant, 5 antibacterial, 6 and molluscicidal. 2 As part of our ongoing investigations on Elaphoglossum species, we examined the diethyl ether (Et 2 O) extract of E. lindbergii to isolate 4 new acylphloroglucinols.…”
Section: Introductionmentioning
confidence: 99%
“…The vermifuge activity of Dryopteris species has been related to the presence of phloroglucinol derivatives in extracts of these plants (Socolsky et al 2009). Characteristic phloroglucinol derivatives, such as aspidin (1) and flavaspidic acid (2) have been reported as major constituents of the genus Dryopteris, and they have been found to possess antioxidant, antibacterial, and antitumor promoting activities (Na et al 2006;Lee et al 2003;Kapadia et al 1996).…”
Section: Introductionmentioning
confidence: 99%